Estudio reológico de las chichas de Yuca (manihot esculenta crantz) y chonta (bactris gasipaes) con preparados enzimáticos - Guanoluisa Ataballo, Tania Mireya (2021)
This research determined the rheological study of cassava chichas (Manihot Esculenta Crantz) and chonta (Bactris Gasipaes) with enzymatic preparations. Where the drinks with enzymatic preparations were determined as the best treatments taking into account the physical-chemical parameters (ºBrix, pH, acidity, and alcoholic degrees), data that were determined in a period of 0 to 72 hours during fermentation, in order to validate results in the process of elaboration and fermentation of ancestral beverages, resulting in burnt chicha ° Bx 18; pH 3.50; acidity 0.68 ° D and finally with the content of alcoholic degrees 5.2% vol. Chicha Blanca ° Bx 13; pH 5.25; acidity 0.68 ° D and finally with an alcohol content of 4.1% vol. Chicha Wiwis ° Bx 12.2; pH 4.5; acidity 0.59 ° D and finally with an alcohol content of 2.9% vol. Chicha de Chonta ° Bx 8; pH 4.25; the acidity of 0.44 ° D and finally with an alcohol content of 4.9% vol. For the rheological study of the fermented beverages, the rotary rheometer of Anton Paar from the laboratory (La Conal, Setlab) was used through the concentric cone type CC27 geometry and parallel plate type PP25 geometry, the appropriate methodology was identified for the rheological analysis of the drinks, in which the density (ρ), apparent viscosity (μ), consistency index (k), behavior index (n), deformation stress (τ) and deformation speed (γ) were determined. Where the calculations were made for the graph of the linear regression coefficient for the rheological index (n), and the apparent viscosity μa (Pa.s) was made with the equation (see equ. 3). The evaluation of each treatment was carried out at a temperature of 17.9 ° C with a relative humidity of 59.6% RH, where the chichas of yucca and chonta that contained enzymatic preparations stood out, yielding the following results: chicha burned with a density of ρ = 1.0319 g / cm3, apparent viscosity μ = 0.18 cP, consistency index k = 0.0138 Pa.s, flow behavior n = 0.0004 adi, shear stress τ = 0.0138 Pa and strain rate γ = 77 (1 / s). Followed by white chicha with a density ρ = 1.0124g / cm3, apparent viscosity μ = 1.13 cP, consistency index k = 0.1072 Pa.s, flow behavior n = 0.0305 adi, shear stress τ = 0.1203 Pa and strain rate γ = 50 (1 / s). Subsequently for the chicha wiwis it presents a density ρ = 1.0280 g / cm3, apparent viscosity μ = 2.92 cP, consistency index k = 0.2203 Pa.s, flow behavior n = 0.0021 adi, stress of shear τ = 0.2223 Pa and strain rate γ = 76 (1 / s). Finally, chonta chicha has a density of ρ = 1.0207 g / cm3, apparent viscosity μ = 1.13 cP, consistency index k = 0.0122 Pa.s, flow behavior n = 0.0020 adi, stress shear τ = 0.0123 Pa, and strain rate γ = 50 (1 / s). That is why fermented yucca and chonta drinks presented the rheological index of a non-Newtonian fluid with pseudoplastic characteristics n> 0; for this reason, that the presence of enzymes in chichas was positively influenced in their elaboration, improving the quality and sensory characteristics of beverages; itself, increased the soluble solids content for the best fermentation process.